2006
DOI: 10.1002/ejic.200600485
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Molecules Containing Metal–Metal Bonds

Abstract: Many chiral compounds having metal-metal bonds are now known in which the M-M unit is the chromophore. In this review they are classified as those where it is either (1) an inherently chiral chromophore owing to helical stacking of metal-ligand bonds, or (2) not inherently chiral but surrounded by a collection of ligands bearing chiral substituents. In only a few cases have the actual CD and/or ORD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 71 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Information on the secondary structures of proteins can be obtained by CD spectroscopy in the far‐UV spectral region (190–250 nm), and CD in the near‐UV region (250–350 nm) can be sensitive to certain aspects of tertiary structure 1b. Near‐UV and visible CD spectroscopy is also used to analyze metal complexes1a,c and the active site of metal‐containing enzymes, such as P450 (300–500 nm), galactose oxidase (300–700 nm), and biotin sulfoxide reductase (300–650 nm) 2…”
Section: Methodsmentioning
confidence: 99%
“…Information on the secondary structures of proteins can be obtained by CD spectroscopy in the far‐UV spectral region (190–250 nm), and CD in the near‐UV region (250–350 nm) can be sensitive to certain aspects of tertiary structure 1b. Near‐UV and visible CD spectroscopy is also used to analyze metal complexes1a,c and the active site of metal‐containing enzymes, such as P450 (300–500 nm), galactose oxidase (300–700 nm), and biotin sulfoxide reductase (300–650 nm) 2…”
Section: Methodsmentioning
confidence: 99%
“…Electrochemical measurements of the Mo2 tetramer in 15a, 15c, and 15d showed stepwise oxidation processes due to Mo2 5+ /Mo2 4+ , while that of 15b and 15e-g showed only one wave. Similarly, cyclic complexes of Rh2 (16, 17, and 18a-g) and Ru2 (19a,b) Some monodentate and bidentate phosphine ligands were used as nonlabile ligands for maintaining the dinuclear units [43,44]. Triphenylphosphine acted as a supporting P-C ligand for [54], amines [55],…”
Section: Paddle-wheel Complexesmentioning
confidence: 99%
“…Edited carbonyl; but the phosphine coordinated to the axial positions of Ru2 moieties to afford phosphine adducts of cyclic dimer (41), trimers (42a,b), and a tetramer (43) (Fig 16) [73]. Edited Jan 14…”
Section: Paddle-wheel Complexesmentioning
confidence: 99%
“…It is, therefore, timely and desirable to develop a new approach for producing neutral metallamacromolecules with welldefined shapes and sizes. Studies reported by Stang [46,47], Cotton [45,[109][110][111], Mirkin [44,50], Severin [66,[112][113][114][115], and Lu [60,61] focused on preparing various neutral functionalized assemblies, some of which showed catalytic activity and selectivity for different sized guest molecules.…”
Section: Introductionmentioning
confidence: 98%